A Patient with AIDS and Embolic Stroke: A Case Report - Troy Fonda; Usman Hadi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Human immunodeficiency virus (HIV) infection is a global concern. Globally, 36.7 million people are living with HIV and 1 million people died at the end of 2016. There is an association between human immunodeficiency virus (HIV) infection with neurological manifestations. Between 1% and 5% of patients with HIV develop stroke. The pathogenesis of AIDS with stroke is still controversial. A 37-year-old male patient with AIDS had an embolic stroke. The diagnosis of the patient was based on clinical condition and the CT scan results of the head with contrast. The stroke-causing mechanism in patients is HIV-associated vasculopathy that results from accelerated atherosclerosis. After administration of antiplatelet and statin, the patient’s condition improves.